2023
DOI: 10.3389/fcimb.2023.1186017
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of macrolide resistance revealed by in vitro selection and genome analysis in Mycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae is an important pathogen causing upper and lower respiratory tract infections in children and other age groups. Macrolides are the recommended treatments of choice for M. pneumoniae infections. However, macrolide resistance in M. pneumoniae is increasing worldwide, which complicates the treatment strategies. The mechanisms of macrolide resistance have been extensively studied focusing on the mutations in 23S rRNA and ribosomal proteins. Since the secondary treatment choice for pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It has also been shown that ribosomal proteins can play a role in antibiotic resistance. Point mutations in the genes of some ribosomal proteins are responsible for acquiring resistance to macrolides and lincosamides ( Prats-van der Ham et al., 2018 ; Na Wang et al., 2023 ). It is possible that in the case of clinical isolates, the upregulation of ribosomal proteins plays an important role in their adaptation to host and requires further study of its role in adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that ribosomal proteins can play a role in antibiotic resistance. Point mutations in the genes of some ribosomal proteins are responsible for acquiring resistance to macrolides and lincosamides ( Prats-van der Ham et al., 2018 ; Na Wang et al., 2023 ). It is possible that in the case of clinical isolates, the upregulation of ribosomal proteins plays an important role in their adaptation to host and requires further study of its role in adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of macrolide resistance have been extensively studied. In addition to erm-mediated rRNA methylation and mef-mediated efflux [ 49 ], emphasis has been placed on mutations in 23S rRNA and ribosomal proteins [ 50 ]. These findings suggest that antibiotic use should be strictly regulated during estrus in animals.…”
Section: Discussionmentioning
confidence: 99%